2019
DOI: 10.1002/qua.25919
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic character of Oh‐C24N24. A cavernous nitride fullerene bearing N4‐macrocycle motifs

Abstract: Spherical fullerenes offer noteworthy structures usually involving six-and fivemembered faces, with application in technological issues. In this sense, cavernous spherical-like structures bearing larger holes provide interesting examples for further understanding of structure-properties relationship. Here, we explored the magnetic response of a proposed cavernous nitride fullerene, C 24 N 24 , which has a O h -symmetry with six N 4 -macrocyclic and eight 1,3,5-triazine faces displaying 48-π electrons. C 24 N 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 74 publications
(80 reference statements)
0
2
0
Order By: Relevance
“…Over time, a multitude of compounds analogous to aromaticity has been found, which has automatically led to a concomitant proliferation of methods and theories to clarify these different characteristics sometimes found in very different compounds. These compounds range from the initial com-pound benzene and its analogs [10,11] to cyclenes, [12][13][14] to various heterocyclic organics, [15][16][17][18][19][20][21][22][23][24] to inorganic compounds [25][26] and Metalla-aromaticity, [27][28][29][30] note here that we mention only some literature on the grounds of too many. According to research on these various aromatic compounds, too many types of aromaticity were defined such as Hückel aromaticity, Möbius aromaticity, Baird aromaticity, σ-aromaticity, π-aromaticity, δaromaticity, multiple aromaticity, excited state aromaticity, transition state aromaticity, three-dimensional aromaticity, spherical aromaticity, cubic aromaticity, octahedral aromatic-ity…, here to mention a few.…”
Section: Introductionmentioning
confidence: 99%
“…Over time, a multitude of compounds analogous to aromaticity has been found, which has automatically led to a concomitant proliferation of methods and theories to clarify these different characteristics sometimes found in very different compounds. These compounds range from the initial com-pound benzene and its analogs [10,11] to cyclenes, [12][13][14] to various heterocyclic organics, [15][16][17][18][19][20][21][22][23][24] to inorganic compounds [25][26] and Metalla-aromaticity, [27][28][29][30] note here that we mention only some literature on the grounds of too many. According to research on these various aromatic compounds, too many types of aromaticity were defined such as Hückel aromaticity, Möbius aromaticity, Baird aromaticity, σ-aromaticity, π-aromaticity, δaromaticity, multiple aromaticity, excited state aromaticity, transition state aromaticity, three-dimensional aromaticity, spherical aromaticity, cubic aromaticity, octahedral aromatic-ity…, here to mention a few.…”
Section: Introductionmentioning
confidence: 99%
“…[ 48 ] This fullerene has six N4 cavities, which are similar to those appear in porphyrine. [ 49 ] These cavities are active sites to host metals by the formation of strong metal‐N covalent bonds. Moreover, several reports have been suggested that metal‐coordinated C 24 N 24 fullerenes show significant catalytic activity toward some reactions.…”
Section: Introductionmentioning
confidence: 99%